2017
DOI: 10.1590/0103-6440201701278
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Malocclusion on Oral Health-Related Quality of Life of 8-12 Years Old Schoolchildren in Southern Brazil

Abstract: The aim of this study was to estimate the impact of malocclusion on the oral healthrelated quality of life (OHRQoL) of schoolchildren aged 8-12 years old in Southern Brazil. A two-stage cluster procedure was used to select 1,199 children in 20 public and private schools in Pelotas/Brazil. Cross-sectional data was collected, consisting of a socioeconomic questionnaire to parents, children's interview and clinical oral examination. The clinical variables were obtained from clinical examination, and the Child Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
2
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 21 publications
8
57
2
10
Order By: Relevance
“…18 Children were categorized into 3 groups of dental caries experience in the permanent dentition (0, 1-4 and >4 number of teeth with dental caries). 13 For the DAI, the reference used for absence of malocclusion was <25 and for presence ≥25, 19 and overjet considered absence was 0-3 mm and presence >3 mm, 20 both used as confounding variables. Traumatic dental injuries were classified using the criteria proposed by Andreasen et al, 21 and they were categorized as the absence of TDI, enamel fracture or enamel-dentin fracture.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…18 Children were categorized into 3 groups of dental caries experience in the permanent dentition (0, 1-4 and >4 number of teeth with dental caries). 13 For the DAI, the reference used for absence of malocclusion was <25 and for presence ≥25, 19 and overjet considered absence was 0-3 mm and presence >3 mm, 20 both used as confounding variables. Traumatic dental injuries were classified using the criteria proposed by Andreasen et al, 21 and they were categorized as the absence of TDI, enamel fracture or enamel-dentin fracture.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…The findings rejected the study hypothesis because, even when the quality of life was evaluated based on the item levels, the anterior occlusal characteristics in the mixed dentition had no impact on the OHRQoL. Previous studies 3,4,7,8,[20][21][22][23][24][25][26][27][28][29] showed that an increased overjet and increased spacing, especially a midline diastema, were the conditions that most affected the individual, regardless of age. Still, the older children become, the more their malocclusion affects their a Values are given as n (%).…”
Section: Discussionmentioning
confidence: 87%
“…Malocclusion in the primary dentition may increase the risk of malocclusion in the mixed and permanent dentition. 23 The upshot is impaired oral health-related quality of life. 24 The findings of a previous literature review 25 reinforce the benefits of adopting exclusive breastfeeding practices and avoiding non-nutritive sucking habits to promote harmonic craniofacial growth, with lifelong benefits.…”
Section: Discussionmentioning
confidence: 99%